The Saqqara letter: historical implications - Smit, E. J. (Journal for semitics, 1990)
The accepted dating of the Saqqara letter is that this plea for help from the Egyptian pharaoh was written during one of the earlier campaigns of Nebuchadnezzar. After the demotic inscription on the reverse of the letter became known, indicating that the letter probably came from Philistine Ekron. a few attempts were made to date the letter almost a century earlier, viz during the reign of Sennachenb. The biggest obstacle to this dating, however, is the reference of the king of Babylon in the letter, and this obstacle seems insurmountable. Not only the mention of the king of Babylon, but also the whole historical background of the late seventh century B.C., especially with reference to the Philistines, and Ekron in particular, serves as the most probable background for dating this letter. Information from Egyptian, Babylonian, and Biblical sources as well as internal evidence based on possible readings of the text are investigated to support this supposition.